2018
DOI: 10.4049/jimmunol.1601386
|View full text |Cite
|
Sign up to set email alerts
|

The Complement C3aC3aR Axis Promotes Development of Thoracic Aortic Dissection via Regulation of MMP2 Expression

Abstract: Thoracic aortic dissection (TAD), once ruptured, is devastating to patients, and no effective pharmaceutical therapy is available. Anaphylatoxins released by complement activation are involved in a variety of diseases. However, the role of the complement system in TAD is unknown. We found that plasma levels of C3a, C4a, and C5a were significantly increased in patients with TAD. Elevated circulating C3a levels were also detected in the developmental process of mouse TAD, which was induced by β-aminopropionitril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…Thus, we tested many pro-inflammatory chemokines and endothelial adhesion molecules which have been validated to be markers of endothelial cells CD40L-CD40 interaction in order to identify endothelial cells dysfunction. Of them, VCAM-1, E-selectin, P-selectin, MCP-1, IL-6, MMP-2 and MMP-9 were previously demonstrated to promote AAD formation [ 3 , 5 , 28 31 ]. DU XM et al observed TNF-α mRNA was elevated in blood samples of AAD patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we tested many pro-inflammatory chemokines and endothelial adhesion molecules which have been validated to be markers of endothelial cells CD40L-CD40 interaction in order to identify endothelial cells dysfunction. Of them, VCAM-1, E-selectin, P-selectin, MCP-1, IL-6, MMP-2 and MMP-9 were previously demonstrated to promote AAD formation [ 3 , 5 , 28 31 ]. DU XM et al observed TNF-α mRNA was elevated in blood samples of AAD patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in ischemic stroke, C3aR was also reported to be implicated in the progression of thoracic aortic dissection and myocardial infarction, which are also vascular diseases [175, 176]. In a model of brain inflammation induced by LPS injection, the results showed that C3aR played a critical role in endothelial activation and leukocyte recruitment when LPS was injected into the brain [177].…”
Section: Complement In Ischemic Strokementioning
confidence: 99%
“…There are a few other studies on complement receptors in thoracic aortic dilatation and dissection. Ren et al has reported systemic complement activation and upregulation of C3aR in human TAA suggesting that the C3a-C3aR1 axis promotes TAA rupture 25. However, their control groups consisted of plasma from healthy volunteers and aortic tissue from patients undergoing heart transplantation without any additional information on the presence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%